Back Cover: Deterministic Integration of hBN Emitter in Silicon Nitride Photonic Waveguide (Adv. Quantum Technol. 6/2021). Issue 6 (8th June 2021) - Elshaari, Ali W.; Skalli, Anas; Gyger, Samuel; Nurizzo, Martin; Schweickert, Lucas; Esmaeil Zadeh, Iman; Svedendahl, Mikael; Steinhauer, Stephan; Zwiller, Val
Abstract : This cover image (referring to article number 2100032 by Ali W. Elshaari and co‐workers) is an artistic representation of hexagonal boron nitride (hBN) single‐photon sources, shown as dipole emitters, deterministically integrated in photonic waveguides. The emitters are encapsulated in the waveguide‐material using plasma enhanced chemical vapor deposition, this is highlighted by peeling the waveguiding layer revealing activated hBN emitters on the substrate. The process is fully deterministic in selecting the quantum sources and their precise placement in any photonic structure, at the same time maintaining the high quality of the emission.